Identification of novel Plasmodium vivax proteins associated with protection against clinical malaria - Mazhari, Ramin; Takashima, Eizo; Longley, Rhea J.; Ruybal-Pesantez, Shazia; White, Michael T.; Kanoi, Bernard N.; Nagaoka, Hikaru; Kiniboro, Benson; Siba, Peter; Tsuboi, Takafumi; Mueller, Ivo (Frontiers in Cellular and Infection Microbiology, 2023)
As progress towards malaria elimination continues, the challenge posed by the parasite species Plasmodium vivax has become more evident. In many regions co-endemic for P. vivax and Plasmodium falciparum, as transmission has declined the proportion of cases due to P. vivax has increased. Novel tools that directly target P. vivax are thus warranted for accelerated elimination. There is currently no advanced vaccine for P. vivax and only a limited number of potential candidates in the pipeline. In this study we aimed to identify promising P. vivax proteins that could be used as part of a subunit vaccination approach. We screened 342 P. vivax protein constructs for their ability to induce IgG antibody responses associated with protection from clinical disease in a cohort of children from Papua New Guinea. This approach has previously been used to successfully identify novel candidates. We were able to confirm previous results from our laboratory identifying the proteins reticulocyte binding protein 2b and StAR-related lipid transfer protein, as well as at least four novel candidates with similar levels of predicted protective efficacy. Assessment of these P. vivax proteins in further studies to confirm their potential and identify functional mechanisms of protection against clinical disease are warranted.